Socialization of planting and the benefits of TOGA for families to increase body immunity during the Covid-19 pandemic in the village of Telaga Bidadari, Sungai Raya District, Hulu Sungai Selatan Regency - Muthmainnah Muthmainnah (UMBanjarmasin, 2021)
COVID-19 as a public health emergency is of international concern. Family Medicinal Plants (TOGA) is a plant that is rich in benefits and is always available in the yard, there are lots of Family Medicinal Plants (TOGA) that can be used to increase body immunity. Covid-19 is a disease that can be transmitted to anyone, so prevention is done by increasing the body's immunity. One way to increase body immunity by consuming TOGA. To get TOGA easily, people can plant it in their respective yards. Moreover, the increase in these cases increasing the price of Toga in the market, one of which is the price of red ginger, because the rhizome is believed to increase the body's immunity